« Théâtre sanglant des perfidies et des massacres » : la topographie parisienne et la mémoire de la Saint-Barthélemy dans la littérature apodémique des XVIIe-XIXe siècles - Ekaterina Bulgakova (Etudes Epistémè)
The current research aims to analyse the role attributed to the memory of Saint Bartholomew’s Day in the topographical and monumental image of the city of Paris, as it was constructed and conveyed by travel literature. The study focuses on printed guidebooks of the 17th and 18th centuries, mostly in French, including works by G. Brice, C. Le Maire, J.-A. Piganiol de la Force, J.-A. Dulaure, as well as volumes which belong to the major 19th-century series published by Galignani, Baedeker and Joanne.Some guidebooks endeavour to present to the readers a « stage » of Saint Bartholomew’s Day, to reconstruct the topography, the timeline and the soundscape of the massacre. The study intends to show in what ways, between a taste for the anecdotal and the moral reflection, between a horror towards and a sinister fascination for « this barbaric execution », apodemic writings from the 17th to the 19th century perceive and try to interpret the traces left by Saint Bartholomew’s Day on the memory map of the capital of France through its architectural monuments, spatial ensembles and works of art. A comparative approach makes it possible to specify in what direction and to what degree the different modes of representing Saint Bartholomew’s Day evolve over time or, on the contrary, are reproduced from one edition to the next, haloed by the prestige of literary tradition.